Trends in Necrotizing Fasciitis‐Associated Mortality in the United States 2003–2020: A CDC WONDER Database Population‐Based Study - Saad Khan (296295) (2025)
Background Necrotizing fasciitis (NF) is a severe and rapidly progressing soft tissue infection with high mortality rates. Despite the urgency of this condition, there is limited research on long‐term NF‐related mortality trends in the United States. Objective This study aims to analyze NF‐related mortality trends in adults aged 25 and older in the United States from 2003 to 2020, focusing on variations by sex, race/ethnicity, and geographic region. Methods NF‐related deaths were identified using the CDC WONDER database through the ICD‐10 code M72.6. Crude and age‐adjusted mortality rates (AAMRs) were calculated across demographic groups and regions. Temporal trends were assessed using the joinpoint regression, providing annual percent change (APC) in mortality rates. Results From 2003 to 2020, a total of 19,158 NF‐related deaths were recorded, marking a 120.6% increase, rising from 824 deaths in 2003 to 1842 in 2020. The overall AAMR increased from 0.44 per 100,000 in 2003 to 0.71 per 100,000 in 2020. Males consistently had higher mortality rates than females and both sexes saw a sharp rise in AAMR after 2015. By race/ethnicity, American Indian or Alaska Native populations exhibited the highest mortality rates, followed by Black or African American individuals. Regional trends revealed that the West had the highest AAMR, whereas the Northeast recorded the lowest. A significant rise in mortality rates was observed across all regions after 2014. Additionally, urban–rural analysis indicated that large central metropolitan areas had consistently elevated mortality rates, whereas smaller metropolitan and noncore areas experienced sharper increases. Conclusions NF‐related mortality has significantly risen in the United States since 2014, with distinct disparities based on sex, race, and geographic region. Contributing factors may include chronic conditions, healthcare access issues, and climate‐related events. Public health interventions focusing on early diagnosis, timely treatment, and addressing healthcare inequities are essential for improving outcomes (highlighted shows corrections). Other Information Published in: World Journal of Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/wjs.12504